Penanaman Ideologi Pancasila pada Anak Usia Dini melalui Film Si Unyil: Analisis Hegemoni Orde Baru - Oktaviani Rahmawati; Siti Fatimah (Jurnal Kronologi, 2026)
This study examines the function of the children's television series "Si Unyil" (1981-1993) as an instrument of state hegemony during the New Order period in Indonesia. The New Order regime systematically utilized mass media as an ideological state apparatus to consolidate power and legitimize its rule. This research addresses two main questions: first, how the concept of "Pancasila society" was manifested and reflected in the series; second, how "Si Unyil" served as a medium for instilling Pancasila ideology in early childhood. Using the historical method encompassing heuristics, source criticism, interpretation, and historiography within Gramsci's hegemony theory, this research analyzes the series' narrative strategies, character construction, and value representations through selected episodes and archival documents. The findings reveal that "Si Unyil" operated as a subtle yet effective propaganda apparatus, employing naturalization and pleasurable learning to internalize Pancasila values. The series constructed an idealized Pancasila society characterized by obedience to authority, social harmony, and uniformity, projecting the state's vision of an orderly society that diverged significantly from the actual social realities of the New Order era, marked by economic inequality and political repression. This study contributes to understanding how authoritarian regimes utilize seemingly apolitical cultural forms children's entertainment to achieve political goals.